Negasi dan Harmoni Pesimisme: Studi Eksposisi Pengkhotbah 1:12-18 dan Manfaat Hikmat Amsal - Manusiwa, Junette Hendrika Martha; Sualang, Farel Yosua (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
One of the wisdom literature books that is frequently quoted, though often interpreted out of context, is the book of Ecclesiastes, which remains relevant to the life of believers. However, there are still differences in interpretation and limitations in historical cultural analysis, as well as varying approaches to textual focus and accountability in understanding life. This article aims to bridge the contradictory aspects of the vanity of wisdom in Ecclesiastes 1:12-18 and its harmony with the benefits of wisdom in the book of Proverbs. The methodology used in this research is wisdom literature hermeneutics, which includes an in-depth textual analysis and historical analysis of the text of Ecclesiastes 1:12-18. This approach provides a bridging understanding that allows for recognizing the contradictions (negation) and harmony in the books of Ecclesiastes and Proverbs, as well as their theological and practical implications for readers. Despite the variety of interpretations, integrating these elements offers a comprehensive view of wisdom and provides a critical reflection both scientifically and practically for real-life application through a relevant, proportional, and balanced theological interpretation in understanding hebel and hokmah. Thus, the awareness of the limitations of human wisdom should be oriented towards complete dependence on the fear of the Lord.